Use and non-use value of wild elephants in Peninsular Malaysia - Poh, Lye Yong; Othman, Mohd Shahwahid; Sius @ Lawrencius, Teddy (Jabatan Perhutanan Semenanjung Malaysia, 2010)
The Contingent Valuation Method (CVM) was used to value both the use and non-use value of wild elephants in Peninsular Malaysia. The use value of wild elephants was estimated through ecotourism services offered by wild elephants at the National Elephant Conservation Centre (NECC) in Kuala Gandah, Pahang. Meanwhile, the non-use value involves ascertaining how much an individual was willing to pay (WTP) to ensure that the existence and heritage attributes of the elephant species are preserved. Structured questionnaires were designed to capture information required for the analysis. To assess the use value of wild elephants, 218 visitors visiting the NECC were interviewed. For the non-use value of wild elephants, a total of 220 random samples were collected via personal interviews to see how society perceive the role of wild elephants as keystone species, in seed disposal, biodiversity conservation and its position as an important component of the ecosystem. This survey was conducted in both urban and rural areas, where people from all walks of life meet, such as shopping areas and coffee shops in four major towns and Taman Negara in the state of Pahang. Results showed that the WTP to NECC was RM 4.30 per visit, while the mean WTP of the Malaysian public to ensure that the elephants' habitat and wellbeing will be protected to meet all their survival needs was RM 5.86 per person. Regression analysis showed that WTP bid was positively related to age in ecotourism services, while income and age were statistically significant in explaining WTP bids in non-use value. The non-use value of wild elephants was higher than use value.